EFEKTIFITAS PEMANFAATAN POTENSI SENYAWA FENOLIK KUBIS UNGU (Brassica Oleraceae var.carpitata. L) SECARA INSTRUMEN UV-VIS - Mamat Pratama; Aminah Aminah; Rizky Arfanita Mas'ud (Faculty of Pharmacy, Universitas Muslim Indonesia, 2018)
Cabbage Purple (Brassica oleracea var. Capitata L.) is one of the genus Brasica genus that is widely available in Indonesia. Purple cabbage has many benefits because it has many content, among others, vitamins A, B, C and E, mineral potassium, calcium, phosphorus, sodium and iron, sulforafan and contain anthocyanin. The purpose of this study was to perform and determine the total phenolic content of purple cabbage (Brassica oleracea var, capitata L.). The method used in qualitative analysis is through color reaction by using specific reagent, while for quantitative analysis done by UV-Vis spectrofotometry method. For antioxidant activity test through absorbance analysis of acid error and sample absorbance from observation result on UV-Vis spectrophotometer. The results of this study contain phenolic compounds, as for the total phenolic content of methanol extracts that the purple cabbage (Brassica oleraceavar, capitata L.) Amounted to 1.9873 mgGAE/g extract.